2022
DOI: 10.2196/42055
|View full text |Cite
|
Sign up to set email alerts
|

Formative Evaluation of the Acceptance of HIV Prevention Artificial Intelligence Chatbots By Men Who Have Sex With Men in Malaysia: Focus Group Study

Abstract: Background Mobile technologies are being increasingly developed to support the practice of medicine, nursing, and public health, including HIV testing and prevention. Chatbots using artificial intelligence (AI) are novel mobile health strategies that can promote HIV testing and prevention among men who have sex with men (MSM) in Malaysia, a hard-to-reach population at elevated risk of HIV, yet little is known about the features that are important to this key population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Unlike the findings by Peng et al [ 14 ], no references were found in interviews expressing concerns about the risk of lack of confidentiality related to the personal information transmitted to Amanda using the Facebook Platform. It is important to point out that the virtual approach can be felt safer, especially in a research context, in which there is a commitment to not reveal user identity and there are explicit security protocols for storing and using research data.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Unlike the findings by Peng et al [ 14 ], no references were found in interviews expressing concerns about the risk of lack of confidentiality related to the personal information transmitted to Amanda using the Facebook Platform. It is important to point out that the virtual approach can be felt safer, especially in a research context, in which there is a commitment to not reveal user identity and there are explicit security protocols for storing and using research data.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, it contributes to the users’ impression of being shielded from prejudgments. By contrast, users may need clarification about the accuracy and safety of information provided by chatbots precisely because they are not humans [ 13 , 14 ]. However, compared with other digital tools, such as apps for health monitoring, chatbots may contribute to improving users’ satisfaction and retention.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study was conducted from June to October 2022, with a predetermined sample size of 200 participants, which included 100 new cases and 100 FU cases. The sample size was determined based on previous studies [ 34 , 35 ]. Upon registration in the rheumatology outpatient clinic, a random sample of patients aged ≥17 years with a diagnosis of AIIRD or a referral for suspected AIIRD was selected.…”
Section: Methodsmentioning
confidence: 99%
“…Using the theoretical framework of Davis [ 10 ] qualitative work with men who have sex with men (MSM) in Malaysia found that the perceived usefulness of chatbots hinged around questions of whether the information provided by the chatbot was accurate, and whether or not it could provide emotional support. Ease of use was influenced by considerations of cost, convenience of access, and software bugs [ 11 ]. Similar results were obtained from focus group discussions with cis-gender female sex workers in South Africa who were found to be open to chatbots and other mHealth tools for HIV care.…”
Section: Hiv Prevention and Carementioning
confidence: 99%